The determination of some biochemical parameters in rats treated with different doses of indomethacin - İzzet Karahan; İbrahim Pirinçci; Bülent Elitok; Ahmet Ateşşahin (Eurasian Journal of Veterinary Sciences)
This study was carried out to investigate the changes occurring in the levels of serum aspartate transaminase (AST), alanine transaminase (ALT), gamma glutamyl transpeptidase (GGT), alkaline phosphatase (ALP), lactic dehydrogenase (LDH), creatin phosphokinase (CPK), sorbitol dehydrogenase (SDH), total bilirubin (TB), direct bilirubin (DB), total protein (TP), albumin (ALB), triglyceride (TG). glucose (GL) and osmolality (OSM) in rats given wilh three different doses of indomethacin. As materials, eighty-four rats were used. Indomethacin was given intramuscularly at the doses of 2.5, 5.0 and 7.5 mg/kg. The blood samples were collected at 0.5, 1, 2, 4. 8, 12 and 24th hours. These samples were analysed for the biochemical parameters. In conclusion, it was determined that indomethacin increased the levels of AST, ALT. GGT. ALP. LDH, CPK, SDH, TB, DB, GL and OSM in serum of rats experimentally given the different doses of indomethacin. In contrast, indomethacin was established to decrease the levels of TP, ALB and TG in serum of rats.